PARTISIPASI PENGANGGARAN SEBAGAI PEMEDIASI HUBUNGAN KEADILAN PROSEDURAL DENGAN KEPUASAN KERJA STUDI KASUS UNIVERSITAS MUHAMMADIYAH MAGELANG - Zuhriyah, Eny (Universitas Muhammadiyah Magelang, 2007)
Prior on this empirical study to investigate the relationship between procedural justice and job satisfaction. In addition, development of this study is include budgetary participation to act as intervening variable to effect the relationship between procedural justice and job satisfaction. Used data for this study is primary data were collected by survey through mail questionnaire with purposive sampling method. Respondents were selected on this study are staff and official who have authority and responbility in order to process budgetary participation at the Muhammadiyah Magelang University. Questionnaire was mailed to each 65 intended respondents and the questionnaire which prepaid return as much as 48 exemplar. As a result, there was 44 usable questionnaire even though 4 exemplar unusable cause the failure of the respondents to complete thw whole questionnaire. The result show that procedural justice and job satisfaction through budgetary participation as intervening variable. The current empirical study shows that budgetary participation a full mediation fully on the relationship between procedural justice and job satisfaction. The result of path analysis show that procedural justice have direct effect on job satisfaction and indirect effect through budgetary participation as intervening variable.